The use of high humidity disperse fraction of jerusalem artichoke developed by its processing into alcohol in the food extrusion technology - A. Yu. Sharikov; M. V. Turshatov; M. V. Amelyakina; A. O. Solovyev; I. M. Abramova (Аграрная наука Евро-Северо-Востока, 2023)
The chemical composition and agrotechnical characteristics of Jerusalem artichoke (Helianthus tuberosus) determine the wide prospects for its use in various branches of the processing industry, including food biotechnology.   The aim of the study was to determine the possibility to use Jerusalem artichoke processed products from various stages of alcohol production in native form without drying in the technology of extruded products and to assess the impact of the raw material selection stage on extrusion modes and quality indicators of the finished product.   In the course of the experimental work, Jerusalem artichoke tubers were processed into alcohol, samples of the high-moisture dispersed fraction of Jerusalem artichoke were taken from different stages of the process. These fractions were added in an amount of 15 % without pre-drying into the mixture for extrusion based on rice groats. The obtained extrudates were dried and their structural-mechanical, color characteristics and nutritional value were determined. The control sample was without the addition of Jerusalem artichoke additives. It has been established that during the extrusion of test samples, compared with the control, the expansion index and the number of microfractures significantly decrease. These data show that with the addition of Jerusalem artichoke fractions, the samples become less porous, their crispness decreases. The expansion index of all experimental samples decreased by 42-49 %. The maximum hardness of 22.9 N, which is 56 % higher than the control value, was noted for a sample with a fraction taken after the fermentation stage. The use of food additives of Jerusalem artichoke from the stages of hydromechanical processing and after fermentation, added in the amount of 15 % to the mixture for extrusion, significantly, by 52-61 %, increased the content of dietary fiber. More promising is the use of Jerusalem artichoke as an ingredient after a full cycle of its processing into alcohol, which makes it possible to enrich the product with microbiological protein of alcohol yeast biomass and increase the total protein content.